Penggunaan Metode Parafrase untuk Meningkatkan Kemampuan Menulis Parafrase Puisi ke Prosa terhadap Hasil Belajar Siswa Kelas II SMP Al-Ittihat Pekanbaru - Usman, Raja (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2015)
Abstract This reasearch is a class room action reasearch. The aims of this research are to increase students writing ability in paraphrasing poetry to prose and to decribe how paraphrase method increase students writing ability in paraphrasing poetry to prose. The subject of this research is the second grade students of SMP Al-Ittihat Pekanbaru. There are 20 students participated in this research. The topic of the writing is paraphrase poetry to prose. The data of these research were taken from students scores on pre-test and post- test and observation record on students and teacher activity on learning proces cycle I and cycle 2 by using paraphrase method. The result of the study showed that on pre-test only 8 students (40%) reached KKM (Minimum Achievment Criterion) while 12 students (60%) failed. At cycle 1, there are 16 students (20%) reached KKM while 4 students (20) failed. At cycle 2, all students (100%) reached KKM. It is concluded that Paraphrase Method can icrease the second grade students, ability in paraphrasing poetry to prose at SMP Al-Ittihat Pekanbaru.